THE ROLE OF THE AGRICULTURAL SECTOR ON ECONOMIC GROWTH IN INDONESIA - Gina Afriyanti; Ana Mariya; Charita Natalia; Sirat Nispuana; M. Farhan Wijaya; M. Yoga Phalepi (CV. Era Digital Nusantara, 2023)
Finding out how Indonesia's agriculture sector affects economic growth is the goal of this study. This study's methodology makes use of literature reviews, reputable publications and journals, as well as other sources that are pertinent to the issue. Because the agricultural sector serves as a source of food security, a tool for reducing poverty, a source of employment, and a source of community income, it plays a significant role in the development of the national economy, including the regional economy.